PENGARUH TRANSFER FISKAL TERHADAP KETIMPANGAN WILAYAH DI KABUPATEN SUMBA TIMUR - Huruta, Andrian Dolfriandra (Universitas Kristen Satya Wacana, 2016)
This article aims to describe impact of fiscal transfer such as village funds allocation towards regional inequality in East Sumba. This article use data such as gross regional domestic product at 2000 constant prices and realization of village funds allocation from 2008 to 2010. The result shows that village funds allocation has a positive and significant impact to regional inequality. Therefore, it’s necessary to create a generative relationship among developed region with the area behind it to remove regional inequality.